2018
DOI: 10.5978/islsm.18-or-10
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different ceramic primers and surface treatments on the shear bond strength of restorative composite resin to zirconium

Abstract: Type of surface preparation significantly affected the bond strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
(7 reference statements)
1
1
0
Order By: Relevance
“…The result of the present study was supported by a previous study which found that surface roughening by diamond bur yielded the highest bond strength (29) . Another study stated that grinding of the ceramic surface yielded a rougher surface than air abrasion and consequently resulted in higher bond strength (30) .…”
Section: Irregularities On the Zirconia Surface (Figure2)supporting
confidence: 88%
“…The result of the present study was supported by a previous study which found that surface roughening by diamond bur yielded the highest bond strength (29) . Another study stated that grinding of the ceramic surface yielded a rougher surface than air abrasion and consequently resulted in higher bond strength (30) .…”
Section: Irregularities On the Zirconia Surface (Figure2)supporting
confidence: 88%
“…Silane, which is a silane agent, has been reported to contain more 3-MPS than other products, which is convenient for use as a syringe-type [ 53 ]. Z-Prime Plus, which is an MDP primer, has been reported to improve bond strength over other products in previous studies [ 12 , 54 ].…”
Section: Discussionmentioning
confidence: 99%